Paleopathology of soft tissues: what mummies can reveal - Fernández, Pedro L.; Esteban, Jordi; Franco, Agustín (Polish Journal of Pathology, 2019)
Paleopathology is a science located in a crossroad between history, archaeology, anthropology, and medicine an can offer unique historical knowledge by using techniques of traditional pathology as well as other branches of Medicine, which is especially fruitful when applied to ancient subjects in which soft tissues are preserved: mummies.